MUZÍKA OQÍTÍWDÍŃ NÁTIYJELILIGIN TÁMIYINLEW METODIKASÍ - Romanova, S.Y. (SCIENCE and SOCIETY, 2025)
The article discusses the necessity of effectively implementing the initial knowledge of music education in higher education institutions and subsequent educational processes, as well as a methodological approach based on systematic principles.